2008
DOI: 10.4049/jimmunol.181.11.7751
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of TGF-β1 and IL-10 Enables Regulatory T Cells to Completely Suppress Airway Hyperreactivity

Abstract: In allergic airway disease, Treg may play an important role in the modulation of airway hyperreactivity (AHR) and inflammation. We therefore investigated the therapeutic potential of Treg in an Ag-dependent murine asthma model. We here describe that AHR can be completely suppressed by adoptive transfer of Treg overexpressing active TGF-β1. Using mice with impaired TGF-β signaling in T cells, we could demonstrate that TGF-β signaling in recipient effector T cells or transferred Treg themselves is not required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 53 publications
3
39
1
1
Order By: Relevance
“…In contrast, in a house dust-mite-induced model, anti-TGFβ antibodies had no effect on airway remodeling but exacerbated eosinophilia resulting in potentiated AHR (23). More recently, it was shown that TGFβ produced by bone marrow stromal cells that home to the lung during an asthmatic episode, is implicated in reducing the pulmonary allergic inflammatory response (24), which is consistent with other reports that TGFβ plays a protective role in the asthmatic response (9,10,25,26).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, in a house dust-mite-induced model, anti-TGFβ antibodies had no effect on airway remodeling but exacerbated eosinophilia resulting in potentiated AHR (23). More recently, it was shown that TGFβ produced by bone marrow stromal cells that home to the lung during an asthmatic episode, is implicated in reducing the pulmonary allergic inflammatory response (24), which is consistent with other reports that TGFβ plays a protective role in the asthmatic response (9,10,25,26).…”
Section: Discussionsupporting
confidence: 85%
“…Tregs are responsible for maintaining immune homeostasis. They can suppress airway inflammation and improve airway remodeling by restraining excessive T-cell immunity, regulating the balance among Th subsets, and decreasing the production of proinflammatory cytokines (49,50). The phosphorylation of STAT5 is considered critical for both Treg development and maintenance as well as Foxp3 expression (29) and is crucial for constraining Th17 cell development (51).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other reports (6,7), in the absence of CD8-expressing cells, activation of nTregs through GITR in the lungs of recipient mice was shown to be sufficient to abrogate suppression and convert these cells to pathogenic effector cells resulting in the enhancement of lung allergic responses (8). Significantly, GITRL expression in recipients appeared to provide the necessary signals to attenuate suppression, as administration of anti-GITRL antibody prevented rather than enhanced lung allergic responses in association with little increase in levels of IL-13 and maintenance of basal levels of IL-10 and TGF-␤ known to be essential for suppressive activity (12,39).…”
Section: Cd25mentioning
confidence: 99%